Chronic atropine administration diminishes the contribution of vasoactive intestinal polypeptide to heart rate regulation - Kuncová, J; Faitová, S; Capouch, J; Stengl, M; Slavíková, J (Physiological research, 2008)
Vasoactive intestinal polypeptide (VIP) is implicated in the modulation of vagal effects on the heart rate. In this study, the impact of acute and chronic atropine administration on VIP levels in rat heart atria was investigated in relation to heart rate in the course of vagus nerves stimulation. Anaesthetised control and atropinised (10 mg/kg/day for 10 days) rats pretreated with metipranolol and phentolamine that were either given or not a single dose of atropine were subjected to bilateral vagus nerve stimulation (30 min: 0.7 mA, 20 Hz, 0.2 ms). VIP concentrations in the atria were determined after each stimulation protocol. In control rats with or without single atropine administration, the heart rate upon vagal stimulation was higher than in atropinised animals with or without single atropine dose, respectively. VIP concentrations in the control atria were significantly decreased after the stimulation; the decrease was comparable both in the absence and presence of a single dose of atropine. Compared to controls, VIP levels were significantly decreased after chronic atropine treatment and they were not further reduced by vagal stimulation and single atropine administration. Administration of VIP antagonist completely abolished the differences in the heart rate upon vagal stimulation between control and atropinised groups. In conclusion, the data indicate that chronic atropine administration affects VIP synthesis in rat heart atria and consequently it modifies the heart rate regulation.
Keywords: alfa blokátory; Vagus Nerve; vazoaktivní intestinální peptid; Phentolamine; nervus vagus; Electric Stimulation; Heart Rate; krysa rodu Rattus; Metipranolol; beta blokátory; receptory muskarinové; zvířata; antagonisté muskarinových receptorů; Heart Atria; Adrenergic alpha-Antagonists; potkani Wistar; časové faktory; antagonisté hormonů; Rats, Wistar; srdeční frekvence; Atropine; atropin; Vasoactive Intestinal Peptide; srdeční síně; Rats; Receptors, Muscarinic; Animals; elektrická stimulace; Hormone Antagonists; fentolamin; Adrenergic beta-Antagonists; Time Factors; Muscarinic Antagonists; metipranolol